Perception about Pain Relief During Normal Labour Among Health Care Providers Conducting Delivery - Tasnim, Saria (Medicine Today, 2010)
Pain during labour is a physiological phenomenon that varies in intensity among women and subjected to many social and cultural modifiers. The objective of the study was to explore the perception and practice of the primary level health care providers who conducts normal vaginal delivery regarding pain relief during labour. A cross sectional questionnaire survey was done at institute of child and mother health during May and June 2009 among a group of senior staff nurses and family welfare visitors. Among 97 respondents 75.3% were senior staff nurses and 24.7% were Family welfare visitors. Only 6.2% thought a women with labour pain should receive an analgesic, 7.4% gives an analgesic and 10.5% reported to receive such drug during their own childbirth. About 58.6% reported to use injection hyoscine butyl bromide and 6.9% uses injection Pethidine analgesia during labour. Forty percent reported to carry out some activity to comfort women in labour. Those were giving assurance (88.7%), explaining the mother about the process of labour (84.5%) and 77.3 % would allow companion in the labour room. About two thirds respondents thought that pain relief may delay progress of labour, 69.5% apprehend fetal distress while 60% are of the opinion that women should endure the natural pain. Key words: Analgesia; labour pain; supportive care; health care provider DOI: 10.3329/medtoday.v22i1.5600 Medicine Today Vol.22(1) 2010. 20-23